THE INFLUENCE OF CORPORATE IMAGE, PERCEIVED SERVICE QUALITY, AND PERCEIVED VALUE TOWARD WORD OF MOUTH WITH COSTUMER SATISFACTION AS MEDIATING VARIABLE (CASE STUDY IN NATASHA SKIN CARE CLINIC PONTIANAK) - Rezki, Amanda Tiara (Jurnal Manajemen Update, 2018)
ABSTRACTFor sustainability of the company, business should be more customers oriented than profit oriented. In determining and selecting a product or service, customers have their own trusted brand. They will trust and loyal to that brand only if they satisfy with the product or service offered by the company. A satisfy customers tend to spread positive word of mouth communication regarding to product or service that they have experienced before. The study aimed to figure out the influence of corporate image, perceived service quality, and perceived value toward word of mouth mediating to customer satisfaction on Natasha Skin care Clinic in Pontianak. Primary data was gathered using questionnaire based on 100 respondents of Natasha in Pontianak. Model analysis used is Structural Equation Model and path analysis. The result of the first test showed that corporate image and perceived value significantly influence the customer?s satisfaction, while perceived service quality is not. Corporate image has not significantly influence word of mouth, while perceived service quality and perceived value is significantly influence. The result of the second test showed that customer satisfaction significantly influence the word of mouth. The result of direct and indirect influence testing which proves the total effect is greater than the direct effect is the influence of Corporate Image, Perceived Service Quality, and Perceived value toward Word of Mouth. This proves that Customer Satisfaction as a mediating variable is able to strengthen the independent and dependent variables. Key word: corporate image, perceived service quality, perceived value, customer satisfaction, word of mouthReferencesAbd-El-Salam, E., & Shawky, A. (2013). The impact of corporate image and reputation on service quality, customer satisfaction and customer loyalty: testing the mediating role. Case analysis in an international service company. The Business & Management Review, 3(2).Arasli, H., Mehtap-Smadi, S. and Katircioglu, S.T. (2005), ?Customer service quality in the Greek Cypriot banking industry?. Journal of managing Service Quality, 15(1), 41-56.Cameran, M., Moizer, P., & Pettinicchio, A. (2010). Customer satisfaction, corporate image, and service qualityin professional services. The Service Industries Journal, 30(3), 421?435.Caruana A, Fenech N (2005). The effect of perceived value and overall satisfaction on loyalty: A study among dental patients. Journal of Medical Mark., 5(3): 245.Chaniotakis and Lymperopoulos, 2009. Service quality effect on satisfaction and word of mouth in the health care industry. Managing Service Quality, 19 (2): 229-242Gurler and Erturgut (2018). The Mediating Effect of Customer Satisfaction on the Relationship Between Perceived Value and Word of Mouth in the Airline Industry. Journal of Business Research Turki, 10 (1), 1-16.Juga, Jari and Juntunen, Jouni (2010). Service quality and its relation to satisfaction and loyalty in logistics outsourcing relationships. Managing Service Quality, 20(6): 496-510Lai Lai T (2004). Service Quality and Perceived Value?s Impact on Satisfaction, Intention and Usage of Short Message Service (SMS). Information systems frontiers, Kluwer Academic Publishers, 6(4): 353-368Lee EJ, Overby JW (2004) Creating value for online shoppers: Implications for satisfactions and loyalty. J. Consum. Satisfaction, Dissatisfaction Compl. Behav., (17): 54-67.McDaniel, JR,C. & Gates, R. (2013). Marketing Research (9th ed.). Hoboken, NJ : John Wiley & Sons Ltd.Methaq, Sallam (2015). THE EFFECT OF CORPORATE IMAGE ON WOM: THE ROLE OF CUSTOMER SATISFACTION AND TRUST. International Journal of economics, commerce and management, 3 (2): 331-340.Ranaweera, C & Prabhu, J. (2003). On the relative importance of customer satisfaction and trust as determinants of customer retention and positive word of mouth. Journal of Targeting, Measurement and Analysis for Marketing 12(1): 82-90.Sallam, Methaq Ahmed Abdulmajid (2015). THE EFFECT OF CORPORATE IMAGE ON WOM: THE ROLE OF CUSTOMER SATISFACTION AND TRUST. International Journal of Economics, Commerce and Management, 3(12), 331-340.Sichtmann, C. (2007). An analysis of antecedents and consequences of trust in a corporate brand. European Journal of Marketing, 41 (9/10), 999-1015Tu, Y., Li, M., & Chih, H. (2013, July). An Empirical Study of Corporate Brand Image, Customer Perceived Value and Satisfaction on Loyalty in Shoe Industry. Journal of Economics and Behavioral Studies, 5(7), 469-483.Türky?lmaz A, Özkan C (2007). Customer satisfaction; Modelling; Mobile communication systems; Turkey. Ind. Manage. Data Syst., 107(5): 672-687.Qin, et al. (2010). Perceived service quality in fast-food restaurants: empirical evidence from China. International Journal of Quality & Reliability Management, 27 (4): 424-437